Characterization of two Epstein-Barr virus epitopes restricted by HLA-B7. - Hill, A; Worth, A; Elliott, T; Rowland-Jones, S; Brooks, J; Rickinson, A; McMichael, A (1995)
We have identified two epitopes for Epstein-Barr virus specific cytotoxic T lymphocytes (CTL) restricted by the common allele HLA-B7. They are EBNA 3C 881-9 (QPRAPIRPI) and EBNA 3A 379-387 (RPPIFIRRL). The epitopes conform well to the recently described motif for HLA-B7-binding peptides (Huckzo et al., J. Immunol. 1993. 151:2572). Titration of the peptides in CTL assays and detergent lysate binding assays revealed that extending the peptides at either the N or C terminus did not reduce their affinity for HLA-B7. This behavior contrasted with HLA-B51, which binds peptides with a similar motif to B7, and has identical amino acid residues at sites expected to form the "F" pocket of the peptide-binding groove. HLA-B51 also bound the peptide EBNA 3C 881-9, but was unable to bind peptides extended at the C terminus.